Effects of Heparin and Related Sulfated Polysaccharides on Tissue Factor Expression Induced by Mitogenic and Non-mitogenic Factors in Human Vascular Smooth Muscle Cells - Xuereb, J. M.; Herbert, J. M.; Sie, P.; Boneu, B.; Constans, J. (Thrombosis and Haemostasis, 1999)
Smooth muscle cells (SMCs) of the intima are generally quiescent and non proliferative. Their proliferation due to different stimulations occurs in myointimal hyperplasia and is regularly present in athero-genesis or after transluminal angioplasty leading to vascular occlusive stenosis. In the course of these pathologies, the Tissue Factor (TF) synthesis was upregulated and rapidly expressed at the membrane of the SMCs. Heparin is known to inhibit SMCs proliferation induced by FCS. We evaluated the inhibitory effect of heparin on the expression of TF induced by various mitogenic (FCS, PDGF-BB and EGF) and non-mitogenic (bacterial LPS) agents. Inhibition by heparin of SMCs proliferation induced by the same agonists was also determined.Quiescent human vascular SMCs from normal adult arteries were treated for 1 h by heparin and related sulfated polysaccharides before stimulation by the agonists. All the agonists up-regulated the expression of TF antigen and activity. TF expression induced by the growth factors was inhibited by heparin (IC 50: 10-30 μg/ml), and other sulfated polysaccharides (IC 50: 1-5 μg/ml). SMCs proliferation, late activation of the extracellular signal-regulated kinases (ERK1/2), and PKC activity were inhibited by heparin (IC 50: 30-50 μg/ml) in SMCs stimulated by FCS but not in SMCs treated by PDGF or EGF. In contrast, heparin had no effect on LPS-induced TF expression nor on LPS-induced PKC activation. These results indicate that, besides its well known effect on SMC proliferation, heparin displays an inhibitory effect on cell mediated blood clotting processes through regulation of the TF expression.